Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 21962 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Leccinum scabrum (Bull.) Gray" ] } The dataset includes 21962 records from 146 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0011463-180824113759888/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences